Development of Environment-Based Digital Flipbook Teaching Materials to Enhance Learning Independence among Elementary School Students - Chaeratunnisa, Elsa; Utari, Enggar; Lestari, Iing Dwi (Universitas Pendidikan Mandalika, 2025)
This study aims to develop environment-based digital flipbook teaching materials to enhance elementary school students' learning independence, particularly on the topic of food chains. The research employed a Research and Development (R&D) method using the ADDIE model. The instruments used in this research included observation, interviews, questionnaires, and learning outcome tests. Data analysis techniques comprised feasibility testing, effectiveness testing, user response testing (students and teachers), and assessment of students' learning independence level. The results show that the digital flipbook was highly feasible, with media expert validation scoring 90.43% and material expert validation scoring 84.37%. The effectiveness test revealed a significant improvement in learning outcomes, with the average pretest score increasing from 55.52 to 90.34 in the posttest, and an N-Gain score of 78.28% (high category). Moreover, student and teacher responses to the flipbook were highly positive, with percentages of 95.47% and 98.33%, respectively. Additionally, students' learning independence significantly increased, reaching 86.89%, which falls into the very high category. These findings suggest that the environment-based digital flipbook is effective in strengthening conceptual understanding of food chains while fostering learning independence through an interactive, contextual, and enjoyable approach.